Kegiatan Eksperimen Sains Sebagai Strategi Menumbuhkan Kreativitas Pada Anak Usia 5-6 Thun - Zulaikah, Siti; Lilif Muallifatul Khorida Filasofa (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2026)
Science experiment activities as a strategy to foster creativity in children aged 5-6 years at TK IT Mona School Semarang. This study aims to analyze the strategy of science experiments in fostering creativity in children aged By using a descriptive qualitative approach, this study provides an in-depth understanding of learning phenomena in the natural environment. Science learning is carried out through a descriptive qualitative approach, providing children with the opportunity to learn directly through simple experiments such as volcanic eruptions and mixing rainbow colors. The program activities are created to encourage critical thinking supporting direct observation to provide meaningful experiences for children. The results of the study indicate that children's active involvement in trying, observing, and drawing conclusions has a positive impact on increasing creativity, especially in aspects of fluency, flexibility and the ability to generate new ideas. The teaching strategies used by teachers, including well-planned activities, open-ended questions, initial demonstrations, have proven effective in helping children think creatively and are able to transform curiosity into concrete scientific understanding. In addition to mastering technical aspects, children also show progress in being responsible and following instructions. Overall, this study concludes that science experiments are an effective, fun, and relevant method for developing creativity in early childhood education environments to integrate the development of cognitive, motor, and social-emotional skills.